PERAN TATA KELOLA DAN SUMBER DAYA TERHADAP BEBAN R&D PERUSAHAAN NONKEUANGAN TERBUKA DI INDONESIA - Joshua Nathanael; Werner Ria Murhadi (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
To accomplish long-term goals, one of the strategic steps taken by the company is investing in innovation through Research and Development (R&D) spending. Numerous studies show that R&D activities can improve company performance. However, fewer studies discuss the factors involved in R&D investment, especially in Indonesia. In addition, the versatile results of previous studies make this research still relevant. This study aims to determine which factors are involved in R&D expense decisions from a company's resource and corporate governance perspective. This research uses multiple linear regression with the Ordinary Least Square (OLS) estimation method. Based on the stability test, the Covid-19 pandemic affects the relationship between several factors in R&D expense. In all samples, only the proportion of independent commissioners positively affects R&D expenses. There is shifting in the variables of company ownership, profitability, and tangible assets toward R&D expense. But, debt has no significant effect on R&D expenses before and during the pandemic. Thus, ownership concentration, independent commissioner, and company resources, such as tangible assets and other financing sources, have a role in the R&D investment decision. This research shows the crucial role of corporate governance in managing a company's resources to sustain a competitive advantage through R&D activities.